The Dynamics of Pretrial Negotiation - Spier, Kathryn E. (Review of Economic Studies, 1992)
A model of sequential bargaining with one-sided incomplete information is analyzed where, if an agreement is not reached, the agents go to court. A "deadline effect" emerges where much settlement occurs just prior to the trial and many cases proceed to court. If fixed costs are incurred during each bargaining period, a "U-shaped" pattern of settlement emerges. These patterns persist in the limit as the time between offers approaches zero. A model with an endogenous trial date is also considered and it is shown that even with complete information there exists inefficient equilibria where disputes are resolved in court. Copyright 1992 by The Review of Economic Studies Limited.